2022
DOI: 10.3390/jmse10040509
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Characteristics of Pore Pressure Coefficient for Two Different Hydrate-Bearing Sediments under Triaxial Shear

Abstract: It is important to determine the volumetric change properties of hydrate reservoirs in the process of exploitation. The Skempton pore pressure coefficient can characterize the process of volume change of hydrate-bearing sediments under undrained conditions during shearing. However, the interrelationship between value responses and deformation behaviors remain elusive. In this study, effects of hydrate saturation and effective confining pressure on the characteristics of pore pressure coefficient are explored s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In general, the pore pressure response rarely causes dramatically post-peak behavior in the slightly OC specimen (i.e., OCR = 2), and its effective path would essentially not move above the CSL; as a result of that, a specimen with OCR = 2 would not exhibit significant dilative behavior [9]. Furthermore, the negative pore pressure response only appears until the accumulated dilatancy is greater than the total contractive deformation in the sediment during undrained shearing [44]. Mayne and Stewart [22] suggested that there is a critical value of OCR greater than ~4 dictating whether a negative pore pressure is generated in the OC specimen.…”
Section: Pore Water Pressure Responsesmentioning
confidence: 99%
“…In general, the pore pressure response rarely causes dramatically post-peak behavior in the slightly OC specimen (i.e., OCR = 2), and its effective path would essentially not move above the CSL; as a result of that, a specimen with OCR = 2 would not exhibit significant dilative behavior [9]. Furthermore, the negative pore pressure response only appears until the accumulated dilatancy is greater than the total contractive deformation in the sediment during undrained shearing [44]. Mayne and Stewart [22] suggested that there is a critical value of OCR greater than ~4 dictating whether a negative pore pressure is generated in the OC specimen.…”
Section: Pore Water Pressure Responsesmentioning
confidence: 99%
“…It was found that the stress–strain curve of HBS was strain-hardening during the shearing process and generated excess pore water pressures (Figure ). , Under undrained conditions, the pore volume of the specimen remains unchanged during the shear, and the water in pore space cannot be drained, making it difficult to change the hydrate distribution mode from pore-filling to load-bearing types. , Thus, undrained conditions limit the contribution of hydrate particles to the strength of HBS. For HBS specimens, the pore pressure increases with the increase of axial strain first, and gradually decreases after reaching the peak strength .…”
Section: Triaxial Shear Testmentioning
confidence: 99%
“…The mechanical properties of hydrate sediments are governed by the hydrate distribution in addition to factors such as net confining pressure, saturation, and mid-major stress coefficient [30]. Hydrate in hydrate sediments exists in three main forms [31], as shown in Figure 3: (i) pore-filling (Figure 4a); (ii) acting as a sediment soil skeleton (Figure 4b), and (iii) cemented between soil particles in the form of colloidal material (Figure 4c).…”
Section: Contact Models and Parametersmentioning
confidence: 99%